Adsorption of iron and manganese from acid mine drainage by zalacca (Salacca zalacca) peel- activated carbon - Eka Anifah; Ismi Khairunnissa Ariani; Janet Tio Panny Tindaon; Basransyah (Sustinere: Journal of Environment and Sustainability, 2024)
The low pH and high metal concentration in acid mine drainage cause environmental problems and affect human health. Adsorption not only removes the pollutants but also increases pH levels. Natural adsorbents have gained attention because of their widespread availability, low cost, and effectiveness. Zalacca peel waste is among the biomass materials showing promise as activated carbon for removing contaminants from acid mine drainage. This study aims to investigate the adsorption capacity of activated carbon from zalacca peel for removing iron and manganese from acid mine drainage. Adsorption studies were conducted in batch experiments using various dosages and contact times. Optimal results were achieved with a dosage of 0.8 grams per 100 mL and contact time of 60 minutes, resulting in 80% removal efficiency for iron and 24% for manganese. The neutralization process occurred post-adsorption, bringing the final pH close to neutral levels, suitable for environmentally safe discharge. Experiment data were fitted to the Freundlich isotherm and pseudo-second order kinetics. FTIR analysis revealed functional groups including C-H, C-O, and C=C was found in the adsorbent. Furthermore, surface area and pore volume experienced slight increases following activation with KOH.